Culinary in Petik Sari Tradition: Meanings and Values along Society Empowerment - Ahmad Zainuri (Universitas Islam Negeri Walisongo Semarang, 2021)
Tradition is a local activity with mystical nuances, a religion that has been around for a long time and flows in people's lives. The purpose of this article is to explain a cultural community tradition with its culinary variety. Community empowerment (rewang) which is represented as a joint movement to build traditions and empower together. In this paper the author uses the socio-religious study method using a phenomenological approach and theoretical framework. This approach is relevant to this study because phenomenology can analyze it to an event that some people might consider normal. However, there are hundreds of meanings that can be expressed in each blade of the Nusantara’s culinary offerings. It is also embedded in the attitude of empowering women, mothers or the entire community so that they can share recipes and cook in a tradition. There is also an educational, spiritual value that will be embedded in every culinary dish of the Nusantara. The theory that I want to use is Auguste Comte’s theory of evolution and Acculturation from Koentowijoyo's point of view. Typical foods in traditions that hold meaning include Jenang, Tumpeng, Takir, and Ingkung Chicken meat. Community empowerment is the key to the preservation of Various traditional culinary delights with their economic, cultural, and historical aspects. Keywords: Tradition, Culinary, Empowered